Autoplay-Based Learning Media Development to Improve Learning Outcomes of Grade IV Elementary School Students - Istiqomah, Lailatul; Mubaligh, Ahmad (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to determine the feasibility, describe the effectiveness, determine the validity and produce Autoplay-based learning media to improve learning outcomes in students’ Hadith al-Qur’an subjects. This type of Research is Research and development (R & D). The development product in this study is Autoplay learning media to improve student learning outcomes. The research design uses the ADDIE approach (analysis, design, development, implementation and evaluation). Data collection techniques with qualitative and quantitative data with T-test. This Research was conducted at MIN 2 Malang City, grade IV students consisting of control and experimental classes. The validity results of material experts obtained 93.75%, media experts 82.14%, and learning experts 90.62%, which means very good. The average value of the control class pre-test was 74.70 and post-test 86.61, while the average value of the experimental class pre-test was 75.29 and post-test 90.88. The difference in learning gains between the experimental and control class post-test scores was 3.53%. So it can be concluded that Autoplay learning media can improve student learning outcomes in Alquran Hadith subjects in class IV MIN 2 Malang.